D&M IS Success Model dan WebQual 4.0 pada Siakad Online STMIK Sinar Nusantara Surakarta - Yovita Kinanti Kumarahadi; Wing Wahyu Winarno; Mei Parwanto Kurniawan (STMIK Sinar Nusantara, 2020)
Decision making must be accompanied by a strong foundation in which knows the net benefits felt by the system user. This study aims to determine the effect of variables on the D&M IS Success Model and WebQual 4.0 in Siakad Online STMIK Sinar Nusantara Surakarta. This research used quantitative method with a questionnaire as a data collection tool. The results show that the research indicators and combination models get significant results. The indicator of research has a significant effect on the combination model. D&M Model IS Success Model and WebQual 4.0 have significance value of 90% and R2 of 84%. It means information quality, system quality, service quality, and website qualityhave significance effects to Siakad Online intention to use and SiakadOnline’s user satisfaction. Then, intention to use and user satisfaction have significance effects to SiakadOnline’s user net benefits. Thus, this combination model is able to describe the relationship between indicators well. Suggestion that can be considered for future research is the addition of other external variables, such as gender.